Project-Based Learning during Covid-19 Pandemic - Wahyuni, Ni Putu Hari (Journal of Educational Study, 2022)
Project-based learning is a learning method that uses projects as a medium. This learning model can be used as an alternative during the pandemic. This study aims at identifying; 1) The implementation of PjBL during Covid-19 pandemic; 2) The advantages of PjBL during Covid-19 pandemic; and 3) The disadvantages of PjBL during Covid-19 pandemic. This research method is library research that collected the data from research articles in national and international journals. Articles are selected based on several criteria. The study found that (1) the implementation of PjBL covers three main steps, they are planning, implementing, and evaluation, (2) there is five advantages of the implementation of PjBL during covid-19, and (3) there is one disadvantage of the implementation of PjBL during covid-19.